University Spin-off for Economic Development in Malaysian Universities - Yasin, Norazlina Mohd; Osman, Mohd Hassan Mohd (International Journal of Economics and Financial Issues, 2015)
The role of universities has been noticed in the last two decades in immediate economic context. Traditionally, universities have emphasized on teaching, research for development, creation and transfer the knowledge. Some universities have taken more active role of starting new businesses and some still are not successfully developed and fulfill their role and demands, because of different factors. In order to develop new entrepreneurial skills and capabilities they need to adopt and learn advanced technologies and market uncertainties and convert this knowledge as an effective tool in spin-off companies. These spin-off companies able to progress capabilities to capitalize knowledge and collaborative network for economic development. In this paper we review Malaysian trend in this context and role of different universities and identifying the abilities they have had to develop and assess their capabilities with organizations networks for their operations. We also illustrated the universities role in economic development and shed a light on government policies and initiative toward university spin-off companies. Keywords: University Spin-off; Entrepreneurship; Knowledge; Economic JEL Classifications: 01